The Palgrave International Handbook of Healthcare Policy and Governance
XX, 696 p.
Keywords: Starting with more general issues of healthcare policy and governance in a global perspective and using the lens of national case studies of healthcare reform, this handbook addresses key themes in the debates over changing healthcare policy.